Transabdominal cervicoisthmic cerclage: initial experience. - Sidhu, H. K. (Ulster Medical Society, 1997)
Pregnancy outcome before and after insertion of transabdominal cervical cerclage is evaluated. The series also reports on the first cases of second pregnancies with the original suture left in situ. It is our view that transabdominal cervical cerclage should only be performed in units that have specialists in Perinatal Medicine.